METHODS FOR ORGANIZATION OF CONTEXTUAL TRAINING OF FUTURE GEOGRAPHY TEACHERS - Karpenko Tetiana; Lakomova Olena; Shyian Daria (Alfred Nobel University Publisher, 2023)
The study examines the issues of improving future geography teachers' professional training through contextual learning; it emphasizes the practicality of conceptual changes in terms of the transition from post-industrial to information society and forced distance interaction. The purpose of the article is to study the features and determine the crucial principles, approaches, stages and technologies of organizing contextual learning for future geography teachers as an organic part of their professional training. Several research methods were used to achieve the goal, including the method of comparative, substantive and reflective analysis of primary sources, advanced domestic and foreign experience, modelling, systematization and concretization of known approaches in the organization of contextual learning of future geography teachers. As a result of the review of scientific literature, the presence of two concepts of contextual learning, which are used in foreign and domestic educational practice, has been revealed. The first model of Contextual Teaching and Learning proposes the involvement of students in the learning process using real, personally meaningful situations and contexts that reflect the application of knowledge and skills in everyday life. The second is A. Verbytskyi's model of Symbolic-Contextual Learning focusing on the assimilation of the professional context by future specialists and presuming the introduction of study material to the scope of future professional activity. It has been pointed out that both models emphasize the importance of the context in the assimilation of effective knowledge and the formation of competence in their application in practice. While the Symbolic-Contextual Learning model is mostly focused on preparing for the future professional activity of a specialist with a higher education level, the Contextual Teaching and Learning one covers a wider application of contexts in the study process of educational institutions of various levels. The content and essence of subject and social contexts for future geography teachers and the ways of their creation in the process of bachelor's professional training have been revealed. The principles and approaches which the technology of contextual learning in the higher pedagogical school is based on have been clarified; the stages (educational activities of the academic type, quasi-professional and study-professional activities), the leading models of contextual learning (semiotic, imitative and social ones), methods, forms and techniques that are most appropriate at each of the stages have been described. The educational and professional training program for bachelors in the speciality 014.07 Secondary education (Geography) at the Kryvyi Rih State Pedagogical University has been analysed; its meaningfulness, efficiency and effectiveness in achieving the program learning outcomes planned by the Standard have been emphasised. It has been claimed that the method of contextual learning is based on student-centred and competency-based approaches and includes: the problem-searching nature of students' educational activities, the use of collaborative learning technologies, ICT and digital technologies, the involvement of external stakeholders, the creation of emotional and moral situations, and the introduction of practice-oriented and interdisciplinary approaches, reflective and analytical assessment. It has been concluded that the integration of traditional and innovative approaches, and the introduction of contextual learning will allow future geography teachers not only to deeper learn the theoretical aspects of geographical and pedagogical sciences but also to skilfully apply them in real life and professional situation.